2019
DOI: 10.1261/rna.071290.119
|View full text |Cite
|
Sign up to set email alerts
|

Efficient electroporation of neuronal cells using synthetic oligonucleotides: identifying duplex RNA and antisense oligonucleotide activators of human frataxin expression

Abstract: Oligonucleotide drugs are experiencing greater success in the clinic, encouraging the initiation of new projects. Resources are insufficient to develop every potentially important project, and persuasive experimental data using cell lines close to disease target tissue is needed to prioritize candidates. Friedreich's ataxia (FRDA) is a devastating and currently incurable disease caused by insufficient expression of the enzyme frataxin (FXN). We have previously shown that synthetic nucleic acids can activate FX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…FRDA patient induced pluripotent stem cells (iPSCs) were cultured in mTeSR1™ medium (STEMCELL Technologies, Cat# 05850) as described earlier ( 42–44 ). Monolayer NPCs were generated and cultured by using the STEMdiff™ Neural System (STEMCELL Technologies, Cat# 08582, 05833) as described in ( 27 ). Briefly, on day 1, the iPSCs were treated with Accutase ® (STEMCELL Technologies, Cat# 07920) and plated in wells precoated with Corning™ Matrigel™ hESC-qualified matrix (Thermo Fisher, Cat# 08774552) at a density of 2 × 10 5 cells/cm 2 in STEMdiff™ Neural Induction Medium + SMADi + 10 μM Y27632.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FRDA patient induced pluripotent stem cells (iPSCs) were cultured in mTeSR1™ medium (STEMCELL Technologies, Cat# 05850) as described earlier ( 42–44 ). Monolayer NPCs were generated and cultured by using the STEMdiff™ Neural System (STEMCELL Technologies, Cat# 08582, 05833) as described in ( 27 ). Briefly, on day 1, the iPSCs were treated with Accutase ® (STEMCELL Technologies, Cat# 07920) and plated in wells precoated with Corning™ Matrigel™ hESC-qualified matrix (Thermo Fisher, Cat# 08774552) at a density of 2 × 10 5 cells/cm 2 in STEMdiff™ Neural Induction Medium + SMADi + 10 μM Y27632.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that formation of stable R-loops at expanded GAA tracts may be responsible for inhibiting transcription progression ( 29 ). Systematic studies of ONs that target GAA–TTC regions clearly demonstrated that both single-stranded and double-stranded ONs reduce formation of R-loops, reverse chromatin changes and elevate FXN transcription in FRDA patient-derived fibroblasts and neuronal progenitor cells (NPCs) ( 27 , 28 , 39 ). Moreover, gapmers targeting GAA repeats for transcript degradation, likely via targeting FXN pre-mRNA engaged in R-loop formation, also augmented levels of FXN mRNA and protein ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cells 2020, 9, x 26 of 45 frataxin expression [171]. Using fluorescent Ca 2+ indicator-loaded brain slices and in vivo samples, the morphology of the apical dendrites of several pyramidal neurons was found to be normal, indicating that the neurons had recovered from the electroporation procedure [172].…”
Section: Electroporationmentioning
confidence: 99%
“…Electroporation was also tested on an organotypic culture of hippocampal slices to introduce plasmids into single-neurons [170]. The approach has been used to demonstrate synthetic oligonucleotides delivery to identify duplex RNA and antisense oligonucleotide activators of human frataxin expression [171]. Using fluorescent Ca 2+ indicator-loaded brain slices and in vivo samples, the morphology of the apical dendrites of several pyramidal neurons was found to be normal, indicating that the neurons had recovered from the electroporation procedure [172].…”
Section: Electroporationmentioning
confidence: 99%
“…ChIP experiments indicate that the activating siRNAs induce small changes in chromatin histone posttranslational modifications on the FXN gene, but have no effect on the recruitment of RNA polymerase II, suggesting that the oligonucleotides relieve a block to transcription elongation through the repeats rather than by increasing pol II occupancy at the promoter [41]. A recent study has also shown efficacy of duplex RNAs and antisense oligonucleotides in neural progenitor cells derived from FRDA induced pluripotent stem cells [86]; however, electroporation of these cells was necessary to see FXN mRNA induction. Future studies will undoubtedly test this approach in animal models for the disease, but a major hurdle will be delivery of nucleic acid therapeutics to the desired target tissues.…”
Section: Epigenetic Drugs To Relieve Fxn Transcriptional Repressionmentioning
confidence: 99%